Theoretical model and playful practice: a pathway to digital accessibility - Binda, Renan; Ribas Ulbricht, Vania (InfoDesign, 2025)
Digital accessibility has often been reduced to merely larger buttons or high-contrast texts; however, it must be approached as a complex cycle involving perceptions, emotions, and values. In this context, technology should serve as a bridge to digital inclusion rather than a barrier. This article examines how a theoretical model for inclusion and digital accessibility can be transformed into an interactive game experience, while also exploring how theory can be gamified to promote inclusive education. Based on a multidimensional theoretical model – which integrates accessibility, usability, functionality, emotion, and value – we discuss the creation of the analog game Jornada da Acessibilidade (Accessibility Journey). Beyond its pedagogical function, the game symbolizes the continuous efforts toward building inclusive digital environments by encouraging user participation in simulations that mirror practical challenges. Preliminary results reveal the potential of gamification in fostering empathy and highlight the necessity to address disabilities beyond the visual and auditory realms. This work serves as an invitation to reconceptualize accessibility as a commitment to human diversity rather than merely a technical requirement.